Systematic review on citation classics in minimally invasive gastrointestinal surgery - Ahmad, Suhaib J. S. (J Minim Access Surg, 2018)
BACKGROUND: The impact an article has on a specific field is manifested by its number of citations. The aim of this systematic review was to perform a citation analysis and identify the 100 most-cited articles in the field of minimally invasive (MI) gastrointestinal (GI) surgery. METHODS: The Institute for Scientific Information Web of Knowledge (1945–2017) was utilised to identify the top 100 most-cited articles in the field of MI GI surgery, using 19 distinct keywords. The data extracted were number of citations, time of publication, research topic, level of evidence, authorship and country of origin. RESULTS: Of the 100 most-cited articles, the number of citations ranged from 3331 to 317 citations. Most publications reported on bariatric surgery (n = 36), followed by oncology (n = 26) and hepatobiliary surgery (n = 15). The studies were published in 26 different journals with the top three journals being Annals of Surgery (n = 30), New England Journal of Medicine (n = 10) and Obesity Surgery (n = 9). The studies were conducted in 17 different countries led by the USA (n = 51), the UK (n = 9) and France (n = 6). Articles were published on all levels of evidence: level I (n = 20), Level II (n = 29), Level III (n = 8), Level IV (n = 29) and Level V (n = 14). CONCLUSION: The study revealed citation classics in the field of MI surgery. Interestingly, a high level of evidence was not significantly associated with an increased citation number.